An application of the service brand verdict model in the evaluation of Japanese household and lifestyle product retail brands - Jasmine A. L. Yeap; T. Ramayah; Yapp, Emily Hon Tshin (Universiti Malaysia Sarawak, 2019)
As new entrants to the Malaysian market, Japanese household and lifestyle product retail brands have successfully gained a strong following among consumers of all ages and ethnicities within a short period of time. This study was conducted to uncover the branding elements which are meaningful to consumers during their experience with such retail brands and to ascertain how consumers’ brand evaluations affect their response, feelings and behaviour towards these brands. Using the Service Brand Verdict Model (SBVM) as a basis, data was collected from 662 customers of a large Japanese brand of household and lifestyle product stores using a self-administered survey. Results from the PLS-SEM analysis revealed that customers’ feelings towards the brand and value-for-money are key components affecting their satisfaction towards the brand. Satisfaction positively affects customers’ attitude as well as attachment to the retailer’s brand. Consequently, customers’ satisfaction, attitude and attachment lead to their loyalty towards the brand. In sum, the SBVM has been shown to remain valid and applicable in evaluating more recent retailing concept stores. Furthermore, in building brand loyalty among consumers, aspiring retailers must ensure that their brands appeal to both the consumers’ head (mind; utilitarian needs) and the heart (feelings; emotional needs)